Elevated Carbon Dioxide Altered Morphological and Anatomical Characteristics, Ascorbic Acid Accumulation, and Related Gene Expression during Taproot Development in Carrots - Wu, Xue-Jun; Sun, Sheng; Xing, Guo-Ming; Wang, Guang-Long; Wang, Feng; Xu, Zhi-Sheng; Tian, Yong-Sheng; Hou, Xi-Lin; Xiong, Ai-Sheng (Frontiers in Plant Science, 2017)
The CO2 concentration in the atmosphere has increased significantly in recent decades and is projected to rise in the future. The effects of elevated CO2 concentrations on morphological and anatomical characteristics, and nutrient accumulation have been determined in several plant species. Carrot is an important vegetable and the effects of elevated CO2 on carrots remain unclear. To investigate the effects of elevated CO2 on the growth of carrots, two carrot cultivars (‘Kurodagosun’ and ‘Deep purple’) were treated with ambient CO2 (a[CO2], 400 μmol•mol−1) and elevated CO2 (e[CO2], 3000 μmol•mol−1) concentrations. Under e[CO2] conditions, taproot and shoot fresh weights and the root/shoot ratio of carrot significantly decreased as compared with the control group. Elevated CO2 resulted in obvious changes in anatomy and ascorbic acid accumulation in carrot roots. Moreover, the transcript profiles of 12 genes related to AsA biosynthesis and recycling were altered in response to e[CO2]. The ‘Kurodagosun’ and ‘Deep purple’ carrots differed in sensitivity to e[CO2]. The inhibited carrot taproot and shoot growth treated with e[CO2] could partly lead to changes in xylem development. This study provided novel insights into the effects of e[CO2] on the growth and development of carrots.